NETWORK DEFENSE SYSTEM MONITORING THROUGH A MOBILE APPLICATION - Lalu Muhammad Aryandi Azrin; Abdul Ghofir (IT for Society, 2019)
paper proposed a way to secure and protect pc or laptop remotely via mobile device. These two device communicate by exchanging information or data using database connection. There will be two applications that are developed, windows-based application and mobile application. The proposed scheme used some firewall configuration and log management to complete the process. The firewall configuration will block computer attacks such as Denial of Service. Log management is to generate a specific log file if there is a possible threat. It will then invoke. the windows application to update the database which is regularly accessed by mobile application. It then alerts user on possible attack or threat.